Determinación de enfermedades del tracto urinario en gatos - Chela Chela, Rosa Amauta (2024)
The present research work was carried out in the clinic of the State University of Bolívar Laguacoto II where 40 male and female cats were evaluated, including neutered and sterilized. The present study was carried out with a descriptive statistical analysis for the determination of Urinary Tract Diseases. in Felines, in urine samples, of which the following variables were evaluated: type of crystal, breed, sex, age, body condition, diet, sexual condition, taking into account the signs and symptoms in this species. Giving priority to urine analysis (Urianalysis) where the physical, chemical and sediment condition of the urine was observed, thus diagnosing the different types of crystals and pathologies that have occurred in the evaluated patients. Where the results obtained could be appreciated, the type of crystal most frequently was Struvite, in mixed-breed cats, neutered males aged 1 to 6 years with an ideal weight or overweight, cats that live indoors with a diet of balanced. The percentage of pathologies in this investigation were the following Bacterial Cystitis 30%, Idiopathic Cystitis 17.50%, Urolithiasis 15% and Urethral Obstruction 15%.